(x+8)(x+8)=81

Simple and best practice solution for (x+8)(x+8)=81 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+8)(x+8)=81 equation:


Simplifying
(x + 8)(x + 8) = 81

Reorder the terms:
(8 + x)(x + 8) = 81

Reorder the terms:
(8 + x)(8 + x) = 81

Multiply (8 + x) * (8 + x)
(8(8 + x) + x(8 + x)) = 81
((8 * 8 + x * 8) + x(8 + x)) = 81
((64 + 8x) + x(8 + x)) = 81
(64 + 8x + (8 * x + x * x)) = 81
(64 + 8x + (8x + x2)) = 81

Combine like terms: 8x + 8x = 16x
(64 + 16x + x2) = 81

Solving
64 + 16x + x2 = 81

Solving for variable 'x'.

Reorder the terms:
64 + -81 + 16x + x2 = 81 + -81

Combine like terms: 64 + -81 = -17
-17 + 16x + x2 = 81 + -81

Combine like terms: 81 + -81 = 0
-17 + 16x + x2 = 0

Factor a trinomial.
(-17 + -1x)(1 + -1x) = 0

Subproblem 1

Set the factor '(-17 + -1x)' equal to zero and attempt to solve: Simplifying -17 + -1x = 0 Solving -17 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + -1x = 0 + 17 Combine like terms: -17 + 17 = 0 0 + -1x = 0 + 17 -1x = 0 + 17 Combine like terms: 0 + 17 = 17 -1x = 17 Divide each side by '-1'. x = -17 Simplifying x = -17

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {-17, 1}

See similar equations:

| 3x+126+3x=180 | | 14x+5=360 | | X/20=-6/5 | | 4x+12+2x-9=21 | | y-19=-5 | | (x+2)=27 | | 3x-1=2x+12 | | 5n-6=-11-7+3n+8 | | 50=72-20log(t+1) | | 5/9(F-32)=12 | | 3e^3x-2=15 | | 9x+4(4x-3)=4(6x+4)-4 | | 5-1/2x=11×x | | 2(7m-3)=-34 | | t=128.91+.32m | | 11x-10=360 | | 49-3m=4m+14m | | 109=n^2-2n-11 | | 5(2y+3)=-5 | | X=-9(-1/2)-1 | | 4x+3y+2x+5y= | | 2.3=6.3-0.8x | | 1.5x+5=6x+4 | | y/1=9 | | t(t)=125 | | 2(4a-7)=50 | | 6X^2+2X=15 | | 20/2=2 | | (630/90/?=1 | | 38=4x+8 | | 5=w-8aforw | | 20-4/10x=0 |

Equations solver categories